Diabetes and Hepatitis C: A Two-Way Association - Hammerstad, Sara Salehi; Grock, Shira Frankel; Lee, Hanna J.; Hasham, Alia; Sundaram, Nina; Tomer, Yaron (Frontiers in Endocrinology, 2015)
Diabetes and hepatitis C infection are both prevalent diseases worldwide, and are associated with increased morbidity and mortality. Most studies, but not all, have shown that patients with chronic hepatitis C are more prone to develop type 2 diabetes (T2D) compared to healthy controls, as well as when compared to patients with other liver diseases, including hepatitis B. Furthermore, epidemiological studies have revealed that patients with T2D may also be at higher risk for worse outcomes of their hepatitis C infection, including reduced rate of sustained virological response, progression to fibrosis and cirrhosis, and higher risk for development of hepatocellular carcinoma. Moreover, hepatitis C infection and mainly its treatment, interferon α, can trigger the development of type 1 diabetes. In this review, we discuss the existing data on this two-way association between diabetes and hepatitis C infection with emphasis on possible mechanisms. It remains to be determined whether the new curative therapies for chronic hepatitis C will improve outcomes in diabetic hepatitis C patients, and conversely whether treatment with Metformin will reduce complications from hepatitis C virus infection. We propose an algorithm for diabetes screening and follow-up in hepatitis C patients.